Changes in chronic neck pain following the introduction of a visco-elastic polyurethane foam pillow and/or chiropractic treatment - Laura J. Soal; Charmaine M. Bester; Brandon S. Shaw; Chris Yelverton (AOSIS, 2019)
Background: Sleep ergonomics are increasingly prescribed as an adjunct treatment to chronic neck pain. Postulated benefits to maintaining the ideal sleeping posture are improved tissue repair in and around the facet joints, decrease in tension of associated musculature and better quality sleep. Aim: The purpose of this study was to determine if the inclusion of a visco-elastic polyurethane (VEP) pillow could benefit the chiropractic treatment of chronic neck pain. Setting: The study took place at a chiropractic training clinic in Johannesburg. Method: Participants were randomly assigned to either a chiropractic treatment only group (CHI) (n = 15) or a chiropractic treatment with a VEP pillow group (CHI+P) (n = 15). Both groups underwent six chiropractic treatments spaced at 3-4-day intervals and the CHI+P were provided with a VEP pillow. Baseline and post-test measurements consisted of the initial Numerical Pain Rating Scale (NRS) and the Vernon-Mior Neck Pain and Disability Index (NDI). Results: Both the CHI and CHI+P groups significantly (p ≤ 0.05) improved their NRS (p = 0.001 for both groups) and NDI (p = 0.001 and p = 0.000, respectively) scores. Furthermore, post hoc analysis indicated a significant difference at post-test between the two groups for NRS (p = 0.015), but not for NDI (p = 0.195). The CHI+P demonstrated an improved minimum clinically important difference (MCID) (43% vs. 73% for NRS and 59% vs. 71% for the NDI). Conclusion: Findings of this study suggest that a VEP pillow could be included as an adjunct management tool to chiropractic treatment of chronic neck pain.